Type 1 Cytotoxic T Cells Increase in Placenta after Intrauterine Inflammation - Liu, Jin; Liu, Yang; Panda, Snigdha; Liu, Anguo; Lei, Jun; Burd, Irina (Frontiers in Immunology, 2021)
CD8+ T cells recognize non-self antigen by MHC class I molecules and kill the target cells by the release of proinflammatory cytokines such as interferon gamma (IFN-γ) and tumor necrosis factor alpha (TNF-α). Our group previously reported an increase of CD8+ T‐cell trafficking in the placenta with exposure to Lipopolysaccharides (LPS). CD8+ cytotoxic T cells have been classified into distinct subsets based upon cytokine production: Tc1 cells produce IFN-γ, Tc2 cells produce interleukin 4 (IL-4). Accordingly, the purpose of this research is to analyze the subsets of placenta CD8+ T cells. We hypothesized that LPS injection would induce a change of properties of CD8+ T cell and Tc1/Tc2 ratio. We investigated the subsets of CD8+ T cell infiltration to placenta and their specific function in response to LPS-induced inflammation in a mouse model. At embryonic (E) day 17, pregnant CD-1 dams received an intrauterine injection of 25 µg LPS in100 μl PBS or 100 μl of PBS only. Flow cytometry was used to quantify CD8+ T cells, evaluate the phenotype and subtypes, and detect markers of Tc1 and Tc2 cells in placenta, at 6 hours and 24 hours post injection (hpi). Intracellular staining and flow cytometry were performed to characterize cytokines produced by CD8+ T cells. Standard statistical analysis were employed. After 6 and 24 hours of LPS injection, total CD8 T cells increased (P<0.05). Tc1 cells expanded (P<0.05) in LPS-treated dams compared with the PBS group. The Tc1/Tc2 ratio was significantly higher in the LPS group than the PBS group (P<0.05). The expression of TNF-α and IFN-γ were increased in LPS group both at 6hpi and 24 hpi (P<0.05). We identified functional placental CD8+ T cell subtypes and found a significant increase ratio of Tc1/Tc2. Following IUI, CD8+ T cells induced inflammatory response in the placenta primarily via the production of Type 1 cytokines such as IFN-γ and TNF-α. We have provided evidence of a Tc1-bias response and cytokines in the mouse model of IUI.